2012
DOI: 10.3892/or.2012.1664
|View full text |Cite
|
Sign up to set email alerts
|

P21-activated protein kinase 1 is overexpressed in gastric cancer and induces cancer metastasis

Abstract: Abstract. P21-activated protein kinase (Pak1), a main downstream effector of small Rho GTPases, plays an important role in the regulation of cell morphogenesis, motility, mitosis and angiogenesis. However, the role of Pak1 in gastric cancer metastasis remains unclear. Here, we showed that Pak1 is overexpressed in gastric cancer tissues from 74 patients by immunohistochemistry. Overexpression of Pak1 was associated with metastasis and prognosis of gastric cancer. In addition, overexpression of Pak1 increased ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
30
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(35 citation statements)
references
References 20 publications
5
30
0
Order By: Relevance
“…The structures of PAK1 and PAK4 are different; the N-terminal regulatory region of PAK4 is fairly divergent from PAKs 1e3. For example, deletion of the PAK4 N-terminal regulatory domain (aa 291-591), mutation of its protein binding domain (H19L, H22L), and mutation of its activation loop (S474E) may lead to depression of the PAK4 catalytic domain [15]. Consistent with them, in our study, it was also shown that PAK4 expression level was higher than PAK1 in the same cancer tissue.…”
Section: Discussionsupporting
confidence: 88%
“…The structures of PAK1 and PAK4 are different; the N-terminal regulatory region of PAK4 is fairly divergent from PAKs 1e3. For example, deletion of the PAK4 N-terminal regulatory domain (aa 291-591), mutation of its protein binding domain (H19L, H22L), and mutation of its activation loop (S474E) may lead to depression of the PAK4 catalytic domain [15]. Consistent with them, in our study, it was also shown that PAK4 expression level was higher than PAK1 in the same cancer tissue.…”
Section: Discussionsupporting
confidence: 88%
“…Taken together our findings suggest that gastrins stimulate cell proliferation and migration by activation of PAK1, which in turn activates multiple signaling pathways, including ERK, AKT, and ␤-catenin. Although PAK1 is overexpressed and hyperactivated in gastric and colon cancer (9,31), in vivo studies on the role of PAK1 in normal colon proliferation and its connection to gastrins have not been reported. The aim of this study was to investigate the role of PAK1 in the regulation by gastrin of the proliferation of colorectal mucosa in mouse models in which gastrin or PAK1 expression had been abrogated.…”
mentioning
confidence: 95%
“…Reports have shown that upregulation of UHRF1 is associated with lung cancer malignancy (Unoki et al, 2010) and with late TNM stage and lymph node metastasis in gallbladder cancer (Qin et al, 2014). Previous studies indicate that UHRF1 is regulated by E2F1 in breast and colorectal cancer; increased E2F1 can trigger tumor invasion and metastasis (Engelmann and Putzer, 2012;Kofunato et al, 2012;Li et al, 2012aLi et al, , 2012b. In the study, UHRF1 was one of the central nodes in the network with upregulation of both UHRF1 and E2F1, indicating that UHRF1 and E2F1 may be the key factors in the development of lung cancer in Xuanwei.…”
Section: Discussionmentioning
confidence: 95%
“…A high level of expression of PAK1 can promote the development of several cancers (Li et al, 2012a(Li et al, , 2012bQing et al, 2012;Lu et al, 2013). In NSCLC, PAK1 kinase promotes cell motility and invasiveness through CRK-II serine phosphorylation.…”
Section: Discussionmentioning
confidence: 98%